THE ARMY OF THE REPUBLIC OF UZBEKISTAN ("Conference on Universal Science Research 2023", 2024)
to understand the Armed Forces of the Republic of Uzbekistan O'zbekiston Respublikasi Qurolli Kuchlari, Ўзбекистон Республикаси Қуролли Кучлари), is the name of the unified armed forces of Uzbekistan, consisting of the Ground Force and the Air and Air Defence forces under the defence ministry. Paramilitary units include the National Guard, a Frontier Service and a River Force. It is reported to be the largest and the strongest in Central Asia.